2008
DOI: 10.1128/jvi.00691-08
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of Host Innate Immune Responses during Lethal H5N1 Infection in Ferrets

Abstract: How viral and host factors contribute to the severe pathogenicity of the H5N1 subtype of avian influenza virus infection in humans is poorly understood. We identified three clusters of differentially expressed innate immune response genes in lungs from H5N1 (A/Vietnam/1203/04) influenza virus-infected ferrets by oligonucleotide microarray analysis. Interferon response genes were more strongly expressed in H5N1-infected ferret lungs than in lungs from ferrets infected with the less pathogenic H3N2 subtype. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
167
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(187 citation statements)
references
References 44 publications
16
167
2
2
Order By: Relevance
“…In contrast, 91, 932, 1516 and 1460 public DBA/ 2J genes were found on days 1e4. Similar amounts of regulated genes after infection with influenza A virus have been obtained in other studies (Cameron et al [16] ca. 2300 genes; Rosseau et al [17] ca.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast, 91, 932, 1516 and 1460 public DBA/ 2J genes were found on days 1e4. Similar amounts of regulated genes after infection with influenza A virus have been obtained in other studies (Cameron et al [16] ca. 2300 genes; Rosseau et al [17] ca.…”
Section: Resultssupporting
confidence: 87%
“…A similar observation was made in ferrets infected with high or low pathogenic influenza virus. Interferoninduced genes were activated in both groups to a similar extent [16]. Furthermore, Zou et al [21] described the activation of genes in interferon-treated macrophages of wild type and Ubp43 mutant mice.…”
Section: Innate Immune Response Genesmentioning
confidence: 86%
See 1 more Smart Citation
“…The genes specifically getting up-regulated in response to virus infection were interferon inducible genes, pro-inflammatory cytokines, components of JAK-STAT pathway, NF-ĸB mediated signaling and genes involved in apoptotic mechanism [32][33][34]41,42]. Interactions of these genes with various other proteins involved in signal transduction mechanism have also been elucidated in these studies.…”
Section: Study Of Host Cellular Responses To Influenza a Infection Usmentioning
confidence: 90%
“…Similar microarray based studies in ferrets showed that H5N1 infection induced severe disease that was associated with strong expression of interferon response genes including the interferon-γ-induced cytokine CXCL10. Treatment of H5N1-infected ferrets with an antagonist of the CXCL10 receptor (CXCR3) reduced the severity of the flu symptoms and the viral titers compared to the controls, clearly demonstrating the potential of biological response modifiers for the clinical management of viral infections [41].…”
Section: Study Of Host Cellular Responses To Influenza a Infection Usmentioning
confidence: 99%